Obsessive Compulsive Disorder with Intellectual Disability: A Diagnostic and Therapeutic Challenge - PRIYANKA GAUTAM; M.S. BHATIA (Journal of Clinical and Diagnostic Research, 2015)
Obsessive compulsive disorder (OCD) are known to occur in patients with intellectual disability and at rates least proportional to the general population but often the developmental disabilities and lack of communication in these patients make it difficult to diagnose and assess the disorder and hence go undetected and untreated. Once diagnosed, treating OCD is another challenge faced by therapist in patients with intellectual disabilities. We report a case of intellectual disability with OCD highlighting the diagnostic and therapeutic challenges.